A Palynology and Classification Study of Some Species in Apocynaceae family at Yala Rajabhat University, Thailand - Chelong, Isma-ae; Aulia, Fera; Bintari, Cesaria Nawang; Hanum, Fanisa Tsabila (YRU Journal of Science and Technology, 2016)
The pollen morphology of 5 species such as Adenium obesum Roem. & Schult., Allamanda cathartica L., Ervatamia coronaria (Jacq.) Stapf, Plumeria alba L. and Wrightia pubescens Blume belonging to apocynaceae family has been examined by light microscopy microscope. Generally pollen grains occur singly in monads. Pollen grains generally spheroidal shape, isopolar and radial symmetry. However, P/E ratio, size, aperture, and tectum of apocynaceae species are differential characteristics. Thus, they can classify with palynological study.